2010
DOI: 10.1089/ten.tea.2009.0659
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Decellularized Lung Bioreactor System for Bioengineering the Lung: The Matrix Reloaded

Abstract: We developed a decellularized murine lung matrix bioreactor system that could be used to evaluate the potential of stem cells to regenerate lung tissue. Lungs from 2-3-month-old C57BL/6 female mice were excised en bloc with the trachea and heart, and decellularized with sequential solutions of distilled water, detergents, NaCl, and porcine pancreatic DNase. The remaining matrix was cannulated and suspended in small airway growth medium, attached to a ventilator to simulate normal, murine breathing-induced stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
325
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(339 citation statements)
references
References 48 publications
10
325
1
3
Order By: Relevance
“…Similarly, cellular proteins such as cytoskeletal actins, tubulins, and mitochondrial ATP synthase subunit alpha-1 appear to be inefficiently removed by the decellularization process according to the peptide spectral match comparisons in Table I. These and the above examples are universally inconsistent with previous reports that indicate near complete depletion of intracellular components, while retaining key components of the ECM (4,44,46,47). Due to these significant qualitative and quantitative inconsistencies utilizing untargeted LC-MS/MS, we deemed this method insufficient to accurately measure differences in protein levels between the two lung types.…”
Section: Resultsmentioning
confidence: 66%
“…Similarly, cellular proteins such as cytoskeletal actins, tubulins, and mitochondrial ATP synthase subunit alpha-1 appear to be inefficiently removed by the decellularization process according to the peptide spectral match comparisons in Table I. These and the above examples are universally inconsistent with previous reports that indicate near complete depletion of intracellular components, while retaining key components of the ECM (4,44,46,47). Due to these significant qualitative and quantitative inconsistencies utilizing untargeted LC-MS/MS, we deemed this method insufficient to accurately measure differences in protein levels between the two lung types.…”
Section: Resultsmentioning
confidence: 66%
“…The detergentextracted lungs extracted all of the cellular contents from the lung as detected by removal of 4 0 ,6-diamidino-2-phenylindole (DAPI) staining ( Supplementary Fig. S2b), but retained normal microarchitecture 25,26 , including ECMs delineating large vessels surrounded by alveoli, alveolar septae, the characteristic spongy matrix of the lung (Fig. 2a, top) and fine ECM fibrils containing collagen I, III, IV, VI, major collagens in the lung, when analysed by immunofluorescence microscopy ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We treated the mice with LPS for the last 2 days. For decellularization of lung, we perfused the lung with decellularization buffer (0.5% SDS/PBS) for 1 h and cryosectioned it and analysed by Haematoxylin and eosin (H & E) staining and immunohistochemistry 25,26 . We confirmed that the collagen immunofluorescence staining we observed is specific and not due to autofluorescence using a secondary only control (rabbit IgG secondary used for all anti-collagen antibodies) ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Angela Panoskaltsis-Mortari, Ph.D., from the University of Minnesota, gave a presentation entitled "Using Decellularized Matrices for Bioengineering the Lung," in which she presented her work on acellular ECM scaffolds and their use in bioreactors to evaluate the potential of multipotent stem cells to regenerate lung tissue (42). When seeded into these scaffolds under the appropriate growth conditions, iPS can express several lung markers, which illustrates the potential for regenerating lung tissue using autologous iPS cells on decellularized matrices to avoid immune-mediated rejection on subsequent transplantation.…”
Section: Session 2: Embryonic Stem Cells Ipscs and Lung Regenerationmentioning
confidence: 99%